Effect of salt stress on salt accumulation in roots and leaves of two sugarcane genotypes differing in salinity tolerance - García, Marina; Medina, Ernesto (Journal of Tropical Agriculture, 2013)
Soil salinization is one of the main restrictions for sugarcane growth in tropical irrigated agricultural lands. Tolerant genotypes are being used to counteract salinization effects. Mechanisms of salt tolerance include restrictions of ion uptake, and compartmentation of ions outside photosynthetic tissues. We determined the Na to K, S, and Cl ratios using X-ray analysis of individual cells of root and leaf tissues of a salt tolerant genotype, PR692176, and a salt sensitive genotype, V-78-1, as a measure of the relative accumulation of ions resulting from salt treatments using sodium sulphate and sodium chloride. Our results showed that root xylem parenchyma is the region where most Na is retained under salinity, and that this retention is more effective in the salt tolerant genotype. In leaves, mesophyll and bundle sheath parenchymas were the sites for Na accumulation, and the strongest increases in Na/K ratios were observed in the sensitive genotype. Sodium chloride treatment increased Na/K ratios more markedly than sodium sulphate, and for all tissues addition of Ca to the nutrient solution reduced the increase in Na/K ratios induced by both salt treatments.